Knowledge and Awareness of Enhanced Recovery After Surgery (ERAS) Protocols Among Anesthesiologists: A Multicenter Cross-Sectional Survey - Beste Mutlu Daglioglu; Damla Kaytanci Ozcelik; Aysenur Sumer Coskun; Oyku Irem Subasi (Healthcare, 2026)
Background: Enhanced Recovery After Surgery (ERAS) protocols aim to reduce surgical stress and optimize postoperative recovery, yet anesthesiologists’ knowledge of these protocols remains incompletely characterized. Methods: This cross-sectional survey (May–August 2025) evaluated knowledge of general and surgery-specific ERAS protocols among anesthesiology specialists, faculty, and residents in Turkey using a 37-item questionnaire based on current ERAS Society guidelines; the primary outcome was the continuous knowledge score, with Bloom’s cutoffs applied descriptively. Results: Among 380 participants (72.4% specialists/faculty, 27.6% residents), the mean standardized score was 68.5 ± 10.3; 47.6% (95% CI 42.7–52.7%) and 28.2% (95% CI 23.9–32.9%) had moderate and high knowledge, respectively. Professional title was independently associated with knowledge: scores were higher among specialists and faculty than residents (β = 5.92 and 6.79), and residents were less likely than specialists (OR 0.423) or faculty (OR 0.344) to fall in a higher knowledge category. Preoperative knowledge was lower than intraoperative/postoperative scores. Module-specific scores, interpreted descriptively because modules differ in item difficulty and subspecialty exposure, were highest in bariatric (74.6%) and lowest in colorectal surgery (49.8%). Conclusions: Anesthesiologists demonstrated predominantly moderate theoretical ERAS knowledge, with gaps in preoperative optimization and specific modules, indicating that curricula and continuing education may benefit from greater emphasis on these areas.